2011
DOI: 10.1177/197140091102400114
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging in Multiple Sclerosis: The Accuracy of 3D Double Inversion Recovery at 3 Tesla and the Potential for Single Sequence Imaging

Abstract: To compare the accuracy of a three dimensional, T2-weighted double inversion recovery (DIR) sequence with two dimensional fluid attenuated inversion recovery (FLAIR) and dual echo T2 (DE T2) sequences at 3 Tesla in the detection of intracranial demyelinating lesions in patients with known or suspected multiple sclerosis (MS), and to consider the appropriateness of a stand-alone DIR sequence in MS imaging. The studies of 98 patients who underwent imaging with DE T2, FLAIR and DIR sequences for known or suspecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The use of the 3D DIR sequence for lesion segmentation could be considered a limitation of this study, since the DIR sequence is not the ''gold standard'' for white matter lesion detection and segmentation. However, several previous studies have shown that the detection rates of MS lesions on DIR are very similar to FLAIR and similar to or better than T2-weighted images in other brain compartments than the cortex, including the white matter and the deep gray matter [18,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 85%
“…The use of the 3D DIR sequence for lesion segmentation could be considered a limitation of this study, since the DIR sequence is not the ''gold standard'' for white matter lesion detection and segmentation. However, several previous studies have shown that the detection rates of MS lesions on DIR are very similar to FLAIR and similar to or better than T2-weighted images in other brain compartments than the cortex, including the white matter and the deep gray matter [18,[40][41][42][43].…”
Section: Discussionmentioning
confidence: 85%
“…Since there are no gaps between the slices, so 3D scans can easily keep the image quality in term of contrast-to-noise ratio (CNR) providing greater spatial resolution. Three-dimensional MRI sequences, due to the use of smaller slice thicknesses, detect smaller size MS plaques especially cortical lesions more precisely and less flow artifacts compared to two-dimensional sequences [34,36].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, because it was discussed in a previous study that a single DIR sequence may be considered appropriate for MS monitoring, 19 the approach presented in this study could contribute to a minimally time-consuming MR imaging protocol, including the acquisition of postgadolinium images, with only DIR pre-and postcontrast (approximately a 12-minute protocol). On the other hand, such short protocols could have limited sensitivity for treatment-associated complications such as progressive multifocal leukoencephalopathy; therefore, further studies are necessary to analyze the sensitivity of DIR regarding opportunistic diseases.…”
Section: Discussionmentioning
confidence: 99%